Implementasi Blended Learning Melalui Google Classroom Pada Mata Kuliah Media Pembelajaran Geografi - Ningsih, Mega Prani; Hilman, Iman; Guntara, Fuad (UNIVERSITAS NEGERI MAKASSAR, 2020)
Learning is currently still centered on lecturers so that it is not yet effective. Blended learning through google classroom as a learning innovation is expected to help learning be effective. The purpose of this study was to examine 1) the stages of implementing blended learning through google classroom in the Geography Learning Media course and 2) student responses to the use of blended learning through google classroom in the Geography Learning Media course. The method in this research is descriptive method. The analysis technique used is descriptive statistics which are presented in a percentage table. The results of the research are 1) the implementation of blended learning is carried out in five stages, namely, analysis of learning outcomes and materials, designing learning content in google classroom, filling in learning content in google classroom, testing blended learning and evaluating the blended learning process; and 2) The implementation of blended learning through google classrooms received positive responses from students, starting from the good to very good categories, namely 61% -100%. The implementation of blended learning through google classroom is considered effective and needs to be developed to support it in the Geography Media Instructional course.